2017
DOI: 10.3390/ma11010046
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Gallium–Tin-Based Oxide Semiconductors for Thin-Film Transistors

Abstract: We investigated the effects of gallium (Ga) and tin (Sn) compositions on the structural and chemical properties of Ga–Sn-mixed (Ga:Sn) oxide films and the electrical properties of Ga:Sn oxide thin-film transistors (TFTs). The thermogravimetric analysis results indicate that solution-processed oxide films can be produced via thermal annealing at 500 °C. The oxygen deficiency ratio in the Ga:Sn oxide film increased from 0.18 (Ga oxide) and 0.30 (Sn oxide) to 0.36, while the X-ray diffraction peaks corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…From Fig. 2c, Ga 3d peaks are located at 20.2 eV [20]. The Ga and Sn orbital peaks in the full spectra ( Fig.…”
Section: Thin Film and Device Characterizationmentioning
confidence: 86%
See 2 more Smart Citations
“…From Fig. 2c, Ga 3d peaks are located at 20.2 eV [20]. The Ga and Sn orbital peaks in the full spectra ( Fig.…”
Section: Thin Film and Device Characterizationmentioning
confidence: 86%
“…Consequently, the excess electrons in the conductive SnO 2 thin film must be inhibited to achieve the enhancement-mode TFT device. The Sn 3d peaks at 486.4 (Sn 3d 5/2 ) and 494.8 eV (Sn 3d 3/2 ) [20] do not obviously shift after Ga incorporation, indicating the oxidation state of Sn element is not affected evidently, as shown in Fig. 2b.…”
Section: Thin Film and Device Characterizationmentioning
confidence: 90%
See 1 more Smart Citation
“…3c. It is found that the Ga 2p and Sn 3d peaks are observed, which means that the α-GTO thin-film layer is composed of GaO x and SnO x , and the Sn 3d 5/2 peak is the sum of the large Sn 4+ peak and small Sn 2+ peak, which means that SnO 2 is more than SnO, although they are mixed, which is also similar to GTO thin films made under different conditions 13 . Because it was reported that SnO 2 is n-type semiconductor and SnO is p-type semiconductor 23,24 , the α-GTO thin-film layer is overall n-type semiconductor, which is also confirmed by the facts that α-GTO thin-film transistors show n-type transistor characteristics 12 and α-GTO thin-film thermoelectric devices show negative Seebeck coefficients 14 .…”
Section: Discussionmentioning
confidence: 67%
“…They can be fabricated at low temperature and produced on large area with low cost. Particularly, the research on α-GTO thin-film devices is focused for not only thin-film conductors 510 but also thin-film transistors 11–13 and other applications 14,15 . They do not include rare metals such as In, and industrial issues on resource depletion and supply anxiety can be solved.…”
Section: Introductionmentioning
confidence: 99%